Making space for engineering education: the South China Institute of Engineering. Issue 3 (1st September 2016) - Luk, Christine Y. L.
ABSTRACT: This article examines the spatial history of an important engineering school during the Republican-Communist transitional years in modern China. I argue that studying the spatiality of engineering education in twentieth-century China is important for two reasons. First, the development of engineering education is a pedagogical priority for both the Nationalist and the Communist Parties, as engineering has dominated the ways in which modern Chinese leadership envisioned the world and the training of many of its most important leaders. Second, the spatial culture of engineering is a technique of power through which the relationship between technical and nontechnical dimensions of engineering practices can be discerned. Drawing from local newspapers, biographies of architects, art and architectural history, and campus publications, the available evidence suggests that while the campus buildings of Zhongshan University during the Republican era exhibit a Canton-specific Lingnan architectural style, such regional characteristic was absent in the newly constructed buildings at the South China Institute of Engineering, of which Zhongshan University was a constituent college during the early Communist era. In addition to the exterior aesthetic style, I also analyze the interior spatial arrangement of SCIE, where the boundary between teaching venues, experimental sites, and industrial shops was not sharply drawn in Communist China, which highlights the eradication of hierarchy among teachers, students, and workers. The spatial history of an engineering school in South China reveals how the efforts to provide space for engineering education reflect a changing geopolitical order in twentieth-century China.